Bees Making Art: Insect Aesthetics and the Ecological Moment - Kosut, Mary; Moore, Lisa Jean (Humanimalia, 2014)
In many cultural fields honeybees reveal themselves as a highly generative species; one that humans have become dependent on.  Within the backdrop of Colony Collapse Disorder, this essay examines how live bees are used in the production of art works.  Historically, bees have been an absent presence in art as artists have relied upon bees for the raw material they create (wax, honeycomb) and for their metaphorical value. Most recently, bees themselves have become art by being transformed into sculptural objects or employed in collaborative insect/human performances that depend upon their embodied labor and participation. Using a bee-centric approach, we track the bees’ path across human art worlds, attentive to the complex ecological, agricultural, and cultural systems they co-create. These interspecies exchanges testify not only to trends in contemporary art, but larger ideas about animal/human boundaries and contemporary environmental issues.